Case control feasibility study assessing the association between severity of coronary artery disease with Glutathione Peroxidase-1 (GPX-1) and GPX-1 polymorphism (Pro198Leu) - Wickremasinghe, Dinushka (BMC Cardiovasc Disord, 2016)
BACKGROUND: Glutathione peroxidase-1 (GPX-1) activity was reported to be useful marker for monitoring cardiovascular disease. However, accurate assessment of coronary artery disease (CAD) using GPX-1 polymorphism is limited for South Asian population. Present study aim to assess GPX-1activity and GPX-1 polymorphismin patients with coronary artery disease (CAD) who were confirmed with coronary angiography findings and in apparently healthy subjects. METHODS: Case control study was carried out with 85 patients (58 males and 27 females) 40–60 years of age confirmed as having CAD on coronary angiography findings and 85 age and sex matched healthy volunteers as controls. Blood samples were analyzed for erythrocyte GPX-1 activity and GPX-1 polymorphism in both groups and the severity of CAD was assessed using coronary angiography scoring system based on vessel, stenosis and extent score. RESULTS: Coronary angiography scores indicated that erythrocyteGPX-1 cutoff value of 23.9 U/gHb showed a high sensitivity and negative predictive value in ruling out major vessel disease. The GPX-1 Pro198Leu (CT) polymorphism was higher in patients with CAD (25.3 %) when compared to controls (10.7 %). Pro198Leu (CT) genotype showed a 2.84 fold risk for CAD [odds ratio 2.84 (95 % CI 1.15–6.98), p = 0.019]. CONCLUSION: Coronary angiography findings indicated that individuals possessing Pro198Leu (CT) polymorphism were found to be associated with low erythrocyte GPX-1 activity and increased susceptibility for CAD.